Ethacrynic and alpha-lipoic acids inhibit vaccinia virus late gene expression - Spisakova, Martina; Cizek, Zdenek; Melkova, Zora (Antiviral research, 2009)
Smallpox was declared eradicated in 1980. However recently, the need of agents effective against poxvirus infection has emerged again. In this paper, we report an original finding that two redox-modulating agents, the ethacrynic and alpha-lipoic acids (EA, LA), inhibit growth of vaccinia virus (VACV) in vitro. The effect of EA and LA was compared with those of beta-mercaptoethanol, DTT and ascorbic acid, but these agents increased VACV growth in HeLa G cells. The inhibitory effects of EA and LA on the growth of VACV were further confirmed in several cell lines of different embryonic origin, in epithelial cells, fibroblasts, macrophages and T-lymphocytes. Finally, we have analyzed the mechanism of action of the two agents. They both decreased expression of VACV late genes, as demonstrated by western blot analysis and activity of luciferase expressed under control of different VACV promoters. In contrast, they did not inhibit virus entry into the cell, expression of VACV early genes or VACV DNA synthesis. The results suggest new directions in development of drugs effective against poxvirus infection.
Keywords: exprese genu; kyselina ethakrynová; Humans; HeLa buňky; Luciferases; Gene Expression; Blotting, Western; lidé; Vaccinia virus; reportérové geny; Cells, Cultured; Virus Replication; plakové testy; luciferasy; HeLa Cells; antivirové látky; kultivované buňky; Genes, Reporter; Viral Plaque Assay; kyselina lipoová; replikace viru; Antiviral Agents; Thioctic Acid; western blotting; Ethacrynic Acid; virus vakcinie